2021
DOI: 10.1053/j.ajkd.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of COVID-19 in People With CKD: A Systematic Review and Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 43 publications
6
101
1
1
Order By: Relevance
“…Our results corroborated the previous results on the death rate estimated between 15 and 45% [13][14][15][16] and the prevalence of admission in intensive care units [17,18] for CKD patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborated the previous results on the death rate estimated between 15 and 45% [13][14][15][16] and the prevalence of admission in intensive care units [17,18] for CKD patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed the value of eGFR in the death risk assessment for the CKD population for the first time. Previous studies (16,17,18) had shown how the presence of CKD or renal replacement therapy was a risk factor for death during COVID-19, but no studies addressed to assess the baseline value of eGFR in CKD patients from stage III to stage V. Only Carlson et al (12) analysis reported the vulnerability to COVID-19 in CKD according to the five stages. They showed how the risk of death is directly associated with the increasing CKD stage.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with end-stage kidney disease, particularly those undergoinghemodialysis, are known to have a high risk of infection and mortality from COVID-19. 7 Previous randomized controlled trials 3 demonstrated thatparticipants administered with REGEN-COV had reduced risk of COVID-19-related hospitalization and death; however, evidence on the e cacy of REGEN-COV amongpatients with end-stage kidney disease is still limited. [4][5][6] A paper reported that kidney transplant recipients administered withREGEN-COV did not require mechanical respiratory support or escalation of care to the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…Organ specific manifestations, which include the liver and the kidney along with their possible mechanism of injury have been available in literature [ 18 ]. A systematic review and meta-analysis of the published studies indicate that COVID-19 incidence was higher in people receiving maintenance dialysis than in those with CKD not requiring kidney replacement therapy or those who were kidney or pancreas/kidney transplant recipients [ 19 ]. In patients with COVID-19, acute Kidney Injury (AKI) may have an inflammatory etiology mediated by a cytokine storm [ 20 ].…”
Section: Discussionmentioning
confidence: 99%